Efektivitas Penggunaan Visual Learning Tools dalam Pembelajaran Sequence Diagram bagi Siswa SMK Jurusan Rekayasa Perangkat Lunak - Zulkipli, Zulkipli; Syahrian, Ekal; Sauri, Sovian; Rania, Salwa; Amad, Lalu Dafa Al (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine the effectiveness of visual learning tools in improving students' understanding of sequence diagram concepts in vocational high schools majoring in Software Engineering (RPL). The study uses a quantitative approach with a quasi-experimental design involving two groups, namely the experimental group who learned using visual learning tools and the control group who used conventional learning methods. Data were collected through objective tests to measure students' cognitive understanding of sequence diagram concepts. Data analysis was performed using a t-test to determine the difference in average learning outcomes between the two groups. The results showed that students in the experimental group obtained significantly higher scores than the control group. These findings indicate that the use of visual learning tools is effective in improving students' understanding of sequence diagram concepts. Graphic and dynamic visual representations help students model object interactions more concretely, thereby reducing cognitive load and supporting the UML learning process more effectively.